2021
DOI: 10.1021/acs.analchem.1c02591
|View full text |Cite
|
Sign up to set email alerts
|

Low Polarity-Triggered Basic Hydrolysis of Coumarin as an AND Logic Gate for Broad-Spectrum Cancer Diagnosis

Abstract: The ability to accurately diagnose cancer is the cornerstone of early cancer treatment. The mitochondria in cancer cells maintain a higher pH and lower polarity relative to that in normal cells. A probe that reports signals only when both conditions are met may provide a reliable method for cancer detection with reduced false positives. Here, we construct an AND logic gate fluorescent probe using mitochondrial microenvironments as inputs. Utilizing the hydrolysis of a coumarin scaffold, the probe generates flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Previously, we noticed that easily synthesized coumarin derivatives (compound 1–1 in Scheme B) can be hydrolyzed to a single hydrolysate under weakly alkaline and low polar conditions . Thus, we speculate that the coumarin lactone may be labile for HSA catalysis due to the hydrophobic cavity of HSA, which has highly nucleophilic basic residues (lysine [LYS) 199, p K a ∼ 8; tyrosine [TYR) 411, p K a ∼ 7.9–8.7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we noticed that easily synthesized coumarin derivatives (compound 1–1 in Scheme B) can be hydrolyzed to a single hydrolysate under weakly alkaline and low polar conditions . Thus, we speculate that the coumarin lactone may be labile for HSA catalysis due to the hydrophobic cavity of HSA, which has highly nucleophilic basic residues (lysine [LYS) 199, p K a ∼ 8; tyrosine [TYR) 411, p K a ∼ 7.9–8.7).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we noticed that easily synthesized coumarin derivatives (compound 1−1 in Scheme 1B) can be hydrolyzed to a single hydrolysate under weakly alkaline and low polar conditions. 53 Thus, we speculate that the coumarin lactone may be labile for HSA catalysis due to the hydrophobic cavity of HSA, which has highly nucleophilic basic residues (lysine [LYS) 199, pK a ∼ 8; 54 tyrosine [TYR) 411, pK a ∼ 7.9−8.7 55 ). We have previously observed that a twisted intramolecular charge transfer (TICT)-based fluorogenic probe (compound 1−2 in Scheme 1B) exhibited a high affinity for HSA and could stably bind into the hydrophobic cavity of HSA (Figures S1 and S2).…”
mentioning
confidence: 98%
“…Nystatin can induce the increase of mitochondrial polarity. 35 Fluorescence imaging of HeLa cells handled with or without nystatin (10 mM) was performed by confocal laser microscopy (Fig. 6(a1)-( a3) and (b1)-(b3)).…”
Section: Cell Imaging Experimentsmentioning
confidence: 99%
“…21 Moreover, neutral mitochondrial polaritysensitive probes have been rarely reported. 5,35 Meanwhile, a good deal of research studies on polarity focus on single organelle targeting. Therefore, it is promising to design a series of polaritysensitive fluorescent probes with different organelle targeting capabilities through similar mechanisms and chemical structures.…”
Section: Introductionmentioning
confidence: 99%
“…So far, plenty of small molecule fluorescent probes have been developed to distinguish cancer cells from normal cells, on the basis of the difference in the microenvironment between cancer cells and normal cells, such as pH and polarity [6][7][8][9][10] based on the acidity difference in cancer and normal cells. 11 For example, a lysosome-targeted Darrow Red derivative (pK a = 2.4), which showed emission with increasing proton concentrations and no emission or very weak emission at pH = 4.0, was synthesized.…”
Section: Introductionmentioning
confidence: 99%